Answer:
(x - 6)(x + 4)
Step-by-step explanation:
x^2 -2x-24
-24 = -6 * 4
- 6 + 4 = -2
So
x^2 -2x-24 = (x - 6)(x + 4)
f(x) = (3x+5)/7
Step 1:
we write f(x) as y
y=(3x+5)/7
Step 2:
switch y by x and x by y
x=(3y+5)/7
Step 3:
solve for y,
x=(3y+5)/7
multiply both sides by 7
7x=3y+5
subtract 5 from left side
3y=7x-5
divide both sides by 3
y= (7x-5)/3
f⁻¹ (x) =(7x-5)/3
48/12 = 24•2/6•2= 24/6= 12•2/3•2= 12/3= 4/1
In simplest form the ratio is
4 worksheets : 1 student
Answer:
![(f\circ g)(4)=31](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%284%29%3D31)
Step-by-step explanation:
<u>Composite Function</u>
Given f(x) and g(x) real functions, the composite function named fog(x) is defined as:
![(f\circ g)(x)=f(g(x))](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3Df%28g%28x%29%29)
For practical purposes, it can be found by substituting g into f.
We have:
![f(x)=3x+1](https://tex.z-dn.net/?f=f%28x%29%3D3x%2B1)
![g(x)=x^2-6](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E2-6)
Computing the composite function:
![(f\circ g)(x)=f(g(x))=3(x^2-6)+1](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3Df%28g%28x%29%29%3D3%28x%5E2-6%29%2B1)
Operating:
![(f\circ g)(x)=3x^2-18+1](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3D3x%5E2-18%2B1)
Operating:
![(f\circ g)(x)=3x^2-17](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3D3x%5E2-17)
Now evaluate for x=4
![(f\circ g)(4)=3(4)^2-17=48-17](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%284%29%3D3%284%29%5E2-17%3D48-17)
![\boxed{(f\circ g)(4)=31}](https://tex.z-dn.net/?f=%5Cboxed%7B%28f%5Ccirc%20g%29%284%29%3D31%7D)